RECOGNIZING PERSONALITY USING HIPPOCRATES’ PERSONALITY TEST AS THE MATERIAL OF COMMUNICATION LEARNING FOR TAX EXTENSION OFFICER’S FUNCTIONALITY - Suharsono, Agus; Amriani, Tenry Nur (Sanata Dharma University Yogyakarta, 2021)
This research aims to find out how to recognize personality using Hippocrates’ Personality Test as the material of communication learning for Tax Extension Officer’s Functionality. It is interesting to be studied because the main duty of Tax Extension Officer’s Functionality is to communicate with many people with different personalities. This study was a qualitative research with quasi-experiment approach, in which data was obtained through participatory observation and document obtained using questionnaire, and the data obtained was analyzed using inductive logic and the result was presented descriptively. The finding of research shows that recognizing personality, using Hippocrates’ Personality Test, based on F. Littauer’s book entitled Personality Plus as the material of communication learning, can be used to recognize the participants’ personality; in addition participants also can identify personality versus communication. The learning has some weaknesses related to the questionnaire that should be completed in quiet and relaxed condition in order to match the actual personality, because the questionnaire completed in hurry and in tired condition will give less valid response. The strength is related to the ability of recognizing personality and to solve communication problem easily. For the learning to be better the participants are recommended to do so in the morning when the brain is still fresh and they still have sufficient time.